Effects of equilibrium radial electric field on ion temperature gradient instability in the scrape-off layer of a field-reversed configuration. (20th April 2021) - Wang, W H; Bao, J; Wei, X S; Lin, Z; Choi, G J; Dettrick, S; Kuley, A; Lau, C; Liu, P F; Tajima, T
Abstract: Linear and nonlinear effects of the equilibrium radial electric field on the ion temperature gradient (ITG) instability in the scrape-off layer (SOL) of a field-reversed configuration have been studied using gyrokinetic particle simulations for a single toroidal mode. Linear simulations with adiabatic electrons find that the E × B flow shear reduces the growth rate and causes a radial tilting of the mode structure on the toroidal plane. Nonlinear simulations find that the E × B flow shear significantly decreases ITG saturation amplitude and ion heat transport in the SOL by reducing both turbulence intensity and eddy size. The turbulence intensity is determined by fluid eddy rotation, which is the dominant saturation mechanism for the SOL ITG instability with a single toroidal mode number. On the other hand, parallel wave-particle decorrelation is the dominant mechanism for the SOL ITG turbulent transport. A random walk model using the guiding center radial excursion as the characteristic length scale and the eddy turnover time as the characteristic time scale fits very well to the scaling of ion heat conductivity with the E × B flow shear.